Migraine is the most prevalent primary headache in individuals with temporomandibular disorders - Franco, Ana L. [UNESP]; Gonçalves, Daniela A.G. [UNESP]; Castanharo, Sabrina M. [UNESP]; Speciali, José G.; Bigal, Marcelo E.; Camparis, Cinara M. [UNESP] (My University, 2010)
Aims: To assess the prevalence of primary headaches (HA) in adults with temporomandibular disorders (TMD) who were assessed in a specialty orofacial pain clinic, as well as in controls without TMD. Methods: The sample consisted of 158 individuals with TMD seen at a university-based specialty clinic, as well as 68 controls. The Research Diagnostic Criteria for TMD were used to diagnose the TMD patients. HAs were assessed using a structured interview and classified according to the Second Edition of the International Classification for Headache Disorders. Data were analyzed by chi-square tests with a significance level of 5% and odds ratio (OR) tests with a 95% confidence interval (CI). Results: HAs occurred in 45.6% of the control group (30.9% had migraine and 14.7% had tension-type headache [TTH]) and in 85.5% of individuals with TMD. Among individuals with TMD, migraine was the most prevalent primary HA (55.3%), followed by TTH (30.2%); 14.5% had no HA. In contrast to controls, the odds ratio (OR) for HA in those with TMD was 7.05 (95% confidence interval [CI] = 3.65-13.61; P = .000), for migraine, the OR was 2.76 (95% CI = 1.50-5.06; P = .001), and for TTH, the OR was 2.51 (95% CI = 1.18-5.35; P = .014). Myofascial pain/arthralgia was the most common TMD diagnosis (53.2%). The presence of HA or specific HAs was not associated with the time since the onset of TMD (P = .714). However, migraine frequency was positively associated with TMD pain severity (P = .000). Conclusion: TMD was associated with increased primary HA prevalence rates. Migraine was the most common primary HA diagnosis in individuals with TMD.
Keywords: Facial pain; Migraine; Prevalence; Temporomandibular joint; Tension-type headache